2009
DOI: 10.1002/hed.21112
|View full text |Cite
|
Sign up to set email alerts
|

Accessory nerve function after level 2b–preserving selective neck dissection

Abstract: Preserving level 2b during selective neck dissection decreases trauma to the accessory nerve and improves functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 24 publications
(45 reference statements)
5
46
0
1
Order By: Relevance
“…This has been confirmed by Dijkstra et al who demonstrated that the type of neck dissection was directly related to postoperative shoulder pain and functionality, and by Cappiello et al who showed that clearance of the posterior neck triangle increased shoulder morbidity. Moreover, Celik et al stated that, according to their experience, preserving sublevel IIb during selective neck dissection “decreases trauma to the accessory nerve and improves functional results” with optimal outcomes in all 30 patients included in their analysis. Apart from the functional consequence on the shoulder, the skin incision required in neck dissection may have a significant impact on quality of life even in terms of aesthetic results .…”
Section: Discussionmentioning
confidence: 99%
“…This has been confirmed by Dijkstra et al who demonstrated that the type of neck dissection was directly related to postoperative shoulder pain and functionality, and by Cappiello et al who showed that clearance of the posterior neck triangle increased shoulder morbidity. Moreover, Celik et al stated that, according to their experience, preserving sublevel IIb during selective neck dissection “decreases trauma to the accessory nerve and improves functional results” with optimal outcomes in all 30 patients included in their analysis. Apart from the functional consequence on the shoulder, the skin incision required in neck dissection may have a significant impact on quality of life even in terms of aesthetic results .…”
Section: Discussionmentioning
confidence: 99%
“…At present, avoidance of level V dissection in selective neck dissection for N0 cases is routine and greatly contributes in maintaining patient QOL. However, Celik et al reported that performing neck dissection with preservation of level IIb reduced the incidence of trapezius muscle atrophy and shoulder drop to 10% of cases, and that of winged scapula to 3.3%; these rates were lower than those reported by van Wilgen et al Koybaşioğlu et al stated that despite the preservation of level IIb, temporary dysfunction of the spinal accessory nerve can occur, although it may be milder than that resulting from IIb resection. These authors asserted that through the preservation of level IIb, symptoms of shoulder syndrome could be minimized; however, the oncologic safety of level IIb preservation has been questioned.…”
Section: Discussionmentioning
confidence: 92%
“…En cas de nécessité de section du nerf spinal pour des raisons carcinologiques, la conservation des racines du plexus cervical permet de limiter les douleurs [11] (niveau de preuve 4). Lorsque le nerf spinal est conservé, la limitation de l'extension du curage permet de diminuer les douleurs postopératoires [12] (niveau de preuve 4), surtout lorsque les aires ganglionnaires situées au contact du nerf spinal (IIB et V) sont épargnées [13][14][15] (niveau de preuve 4). Le monitoring du nerf spinal pendant la chirurgie cervicale n'a pas fait la preuve d'un intérêt pour diminuer les douleurs postopératoires [16] (niveau de preuve 4).…”
Section: Douleurs Séquellaires De La Chirurgie Ganglionnaireunclassified